Verbal Subscribers of Matin Al- Shatibya: Collection and Study - Majeed, Othman Rashid (Arab Journal for Sciences and Research Publishing, 2020)
This research includes studying the common terms of the book (Hirz Al_Amany wawajih Al_Tahany) for Al- Shatibya. He used terms was repeated in the chapters of his book, every term gives different meaning in it's cheaper and explains these meanings, I followed all words in his book, so I have explained this for everyone needed to study this book from its sources then directed each word to its chapter, I divided it into two research, the first includes Al- Shatiby biography and an explanatory definition of his book, in the second I put the places of this terms and its meanings, explanations and places accommodating which came in the book the directing of it, then I concluded the research, in brief, included the most important results I reach to it.Among the most important results:- Scientific abundance in various sciences of Matin Al- Shatibya.- Repeating the word in different chapters and with multiple uses confuse the student if he is ignorant.- The number of joint words reached seven, resulting in nineteen uses.- Al- Shatibya needs more studies and research, despite its many explanations and oppositions.
Keywords: Al-Shatibi; Al-Shatibiyyah; Common Terminology